Flocculation in a decaying shear field and its implications for mud removal in near‐field river mouth discharges. Issue 4 (1st April 2016) - Strom, Kyle; Keyvani, Ali
Abstract: We measure the change in floc size in a decaying shear field that mimics the decay found in a river mouth discharge. The primary questions explored are: (1) how far from equilibrium are the flocs during the decay? And, (2) how significant are the changes in size, and hence settling velocity, brought on by the changes in shear when it comes to predicting settling flux? These questions are examined in the laboratory using a camera system that allows for flocs to be sized within a turbulent suspension. We also examine how inclusion of various approaches to account for flocculation impacts the plume concentration and deposition rates in a simple river mouth discharge model. In the experiments, flocs grew from their initial size of 20–50 μm up to 100–200 μm due only to changes in shear over time scales of decay similar to those in a small river mouth discharge. It is estimated that such growth would lead to fourfold or greater fold increase in the mud settling velocity within the first few kilometers from the river mouth, even though floc sizes were only 0.5–0.8 of their equilibrium values. The plume modeling highlights the strong dependence of the mud deposition rate on the method chosen to account for flocs, and the importance of the settling to entrainment velocity ratio in dictating plume concentrations. Key Points: Flocs increased in size 4X in experiments that simulated the shear conditions in a river mouth plume Floc sizes were in disequilibrium with local fluid shear and sediment concentration Plume model output is dependent on floc method used and the settling to entrainment velocity ratio